Quo vadis, Domine? - Szabolcsi, Robert (Technium Social Sciences Journal, 2020)
The recent day pandemic events and its consequences in the global world famous for collapsing good many old values and routines forces scientists and scholars to find out what to say in response. Some scientists gave a formula, which is funny for the first hearing, leaning on Baron Münchhausen’s unbelievable narratives, when he pulls himself out of a mire by his own hair. The global shock hitting the world washed out numerous old routines, old solutions, old methods and old tools, however, still there are only few existing answers and only first steps made how to get out from the mire. The purpose of the author is to trigger, to help and to support thinking about the path leading to something new, which is still unknown, having few weakened pillars only, and focusing on the support higher education can establish in this battle.